Nostalgia za klasyką w powieści Manaraga Władimira Sorokina - Stryjakowska, Anna (Studia Rossica Posnaniensia, 2019)
The article discusses Vladimir Sorokin’s novel Manaraga as a metafictional statement concerning the problem of the literary canon. The proposed interpretation places the novel in the post-ironic thinking, within which the value of high culture is still in force.